A comparative cross-sectional study of psychological distress, fatigue, and physical activity in patients with rheumatoid arthritis, systemic lupus erythematosus, and Sjögren's disease - Beider, Sonja; Stephan, Michael; Seeliger, Tabea; Skripuletz, Thomas; Witte, Torsten; Ernst, Diana (Frontiers in Medicine, 2025)
IntroductionAnxiety and depression are common in patients with rheumatic diseases, but their impact across conditions like rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and primary Sjögren's disease (SjD) is still not well understood. This study aims to compare depression, anxiety, and fatigue, and their effects on disease activity and physical activity in these conditions.MethodsFrom January 2019 to March 2021, patients with RA, primary SjD and SLE were assessed consecutively in a monocentric cross-sectional study at the rheumatology outpatient clinic of the Hannover Medical School. Standardized questionnaires were used to assess depression, anxiety, fatigue, disease activity, functional impairment, and physical activity in these patients.ResultsOf 445 patients, 36.9% had RA, 32.8% SLE, and 30.3% SjD, with most being female (RA 76.2%, SLE 85.6%, SjD 87.4%). Depression (28.5%) and anxiety (31.2%) were common, particularly in SLE (28.8%) and SjD (36.3%) vs. RA (22%, p 0.002). Physical inactivity was higher in SLE (44.5%) and SjD (44.4%) than in RA (39.0%), especially in depressed patients (p 0.011). A significant proportion of patients retired early, especially in SLE (85%) and SjD (66%) vs. RA (49%, p 0.001). Disease activity correlated with psychological status (p < 0.05).ConclusionsDepression and anxiety are highly prevalent in RA, SLE, and SjD, particularly in SLE and SjD. The study highlights the need for early psychological evaluation and integrated care involving rheumatologists and mental health professionals to address these issues and improve physical and mental well-being.